2017
DOI: 10.1002/cpp.2092
|View full text |Cite
|
Sign up to set email alerts
|

Insecure attachment and maladaptive schema in disordered eating: The mediating role of rejection sensitivity

Abstract: The results from the current study suggest that insecure attachment leads to maladaptive schema, which in turn leads to sensitivity to rejection and subsequent disordered eating behaviour. Attachment anxiety, but not attachment avoidance, was related to greater endorsement of all five schemas in the disconnection and rejection domain. Path analysis revealed that, of the schema in the disconnection and rejection domain, only emotional deprivation and abandonment were related to disordered eating. Interpersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 47 publications
(80 reference statements)
3
29
1
3
Order By: Relevance
“…Overall, the current findings may be seen as a transdiagnostic risk model for the development of ED and/or BPD symptoms, where the shared underlying factors of emotion dysregulation and abandonment, may predispose individuals to develop symptoms for either disorder. These findings are in line with previous research that has shown emotion dysregulation (e.g., Daros & Williams, 2019; Selby et al, 2010) and abandonment (e.g., Al‐Salom & Boylan, 2019; De Paoli, Fuller‐Tyszkiewicz, & Krug, 2017) to be key predisposing and maintaining factors for ED and BPD symptoms. Interestingly, a new study by Al‐Salom and Boylan (2019) found abandonment to fully mediate the relationship between BPD traits and eating pathology, highlighting its importance in explaining the relationship of both problem sets.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, the current findings may be seen as a transdiagnostic risk model for the development of ED and/or BPD symptoms, where the shared underlying factors of emotion dysregulation and abandonment, may predispose individuals to develop symptoms for either disorder. These findings are in line with previous research that has shown emotion dysregulation (e.g., Daros & Williams, 2019; Selby et al, 2010) and abandonment (e.g., Al‐Salom & Boylan, 2019; De Paoli, Fuller‐Tyszkiewicz, & Krug, 2017) to be key predisposing and maintaining factors for ED and BPD symptoms. Interestingly, a new study by Al‐Salom and Boylan (2019) found abandonment to fully mediate the relationship between BPD traits and eating pathology, highlighting its importance in explaining the relationship of both problem sets.…”
Section: Discussionsupporting
confidence: 91%
“…Although the sociodemographic data and the clinical symptoms of our study are comparable with the majority of AAI/AAP studies (see,e.g., Fonagy et al, , Delvecchio et al, , or Juen et al, , who recruited their samples in psychiatric inpatient units and reported moderate to severe levels of psychopathology), other studies include patients who have currently recovered from their disorder (De Paoli et al, ) or who were not diagnosed with a psychiatric disorder according to DSM criteria (Burns et al, ). Furthermore, some studies did not only recruit their sample in hospitals but by advertisement or from private clinical psychologists (De Paoli et al, ; Ringer & Crittenden, ). Thus, future research might do well to differentiate inpatient and outpatient adolescent samples for symptom severity and for possible comorbidity rates as these variables might have a significant impact on attachment‐specific characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although clinical case studies (Dallos & Denford, 2008;Ringer & Crittenden, 2007) (Burns et al, 2012). Furthermore, some studies did not only recruit their sample in hospitals but by advertisement or from private clinical psychologists (De Paoli et al, 2017;Ringer & Crittenden, 2007). Thus, future research might do well to differentiate inpatient and outpatient adolescent samples for symptom severity and for possible comorbidity rates as these variables might have a significant impact on attachment-specific characteristics.…”
Section: Attachment and Childhood Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Teori yang pertam kali dikembangkan oleh John Bowlby ini kemudian dikembangkan lagi oleh Armsden & Greenberg (1987), yang berfokus pada implikasi optimal serta tidak optimalnya attachment terhadap kesehatan psikologis anak dan remaja. Hal ini karena attachment memiliki pengaruh yang penting bagi remaja untuk mampu mengatasi tantangantantangan yang dialami akibat perubahan (De Paoli, Fuller-Tyszkiewicz, & Krug, 2017). Terlebih lagi, kualitas attachment yang kuat akan menjadi faktor penting bagi remaja dalam menyelesaikan tugas perkembangan yang ada (Gander, Sevecke, & Buccheim, 2015).…”
Section: Latar Belakangunclassified